Analysis green consumption concept from a bibliometric - Sandra Nelly Leyva-Hernández; Paola Miriam Arango-Ramírez; Magaly Gaviria-Marin (Cogent Business & Management, 2024)
The aim of this manuscript is to provide a comprehensive overview of the existing literature on green consumption. Moreover, it proposes future research directions to further expand our understanding of the evolution of the field of green consumption through a bibliometric study approach. The analysis encompasses the period between 1975 and 2021, and employs base data from the Web of Science (WOS). The study scrutinizes publications through a range of bibliometric indicators such as the most cited articles, the most prominent authors, institutions, countries, and the most productive journals. The h-index, productivity, and citations are some of the bibliometric indicators used to assess the publications. Additionally, graphic mapping is presented through the VOS viewer, which facilitates an analysis of authors' co-citation and the keywords' co-occurrence. The findings demonstrate the evolution, integration, and scope of the concept, wherein individuals, communities, and governments play a pivotal role in embracing new practices, policies, and resource utilization. The study concludes that various theories, approaches, and causal variables present challenges concerning consumption and purchasing habits.
Keywords: 650; Ethical consumption; consumer citizenship; green behavior; empowerment; green washing